2018
DOI: 10.3389/fimmu.2018.00119
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hematopoietic MLKL Protects Against Salmonella Mucosal Infection by Enhancing Inflammasome Activation

Abstract: The intestinal mucosal barrier is critical for host defense against pathogens infection. Here, we demonstrate that the mixed lineage kinase-like protein (MLKL), a necroptosis effector, promotes intestinal epithelial barrier function by enhancing inflammasome activation. MLKL−/− mice were more susceptible to Salmonella infection compared with wild-type counterparts, with higher mortality rates, increased body weight loss, exacerbated intestinal inflammation, more bacterial colonization, and severe epithelial ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 61 publications
1
21
2
Order By: Relevance
“…In line with this notion, constitutive IFN signaling has recently been reported to maintain a critical threshold of MLKL expression to license necroptosis [34]. Besides its function in necroptosis, MLKL has been shown to regulate endosomal trafficking and the generation of extracellular vesicles and to contribute to inflammasome activation [35], [36], [37], [38], [39], [40].
Figure 6IRF1 and STAT1 regulate MLKL expression.IFNs like IFNγ bind to their IFN receptor and induce the activation and phosphorylation of STAT1. The transcription factor STAT1 induces the expression of ISGs such as IRF1.
…”
Section: Discussionmentioning
confidence: 81%
“…In line with this notion, constitutive IFN signaling has recently been reported to maintain a critical threshold of MLKL expression to license necroptosis [34]. Besides its function in necroptosis, MLKL has been shown to regulate endosomal trafficking and the generation of extracellular vesicles and to contribute to inflammasome activation [35], [36], [37], [38], [39], [40].
Figure 6IRF1 and STAT1 regulate MLKL expression.IFNs like IFNγ bind to their IFN receptor and induce the activation and phosphorylation of STAT1. The transcription factor STAT1 induces the expression of ISGs such as IRF1.
…”
Section: Discussionmentioning
confidence: 81%
“…This study is important because it demonstrates that necroptoticinduced disease may, in some circumstances, be inhibited by targeting a single downstream inflammatory mediator. More recently, it was reported that MLKL activation in the intestinal mucosa was required for inflammasome-mediated protection against Salmonella infection [104], while Staphylococcus toxin-induced MLKLtriggered NLRP3 activation to promote damaging inflammation [105]. It will be interesting to define which other necroptotic disease models may also respond to NLRP3 inflammasome inhibition, or whether there are other specific DAMPS, such as HMGB1, whose targeting may be useful to limit damaging, necroptoticinduced, inflammation.…”
Section: Necroptotic To Pyroptotic Crosstalk: Is the Nlrp3 Inflammasomentioning
confidence: 99%
“…Moreover, MLKL protects from Salmonella infection promoting intestinal epithelial barrier function by inducing inflammasome activation in IECs. Besides, mice with MLKL ablation are more susceptible to Salmonella infection and present impaired caspase-1 and GSDMD cleavage with consequently decreased interleukin IL-18 release [ 70 ].…”
Section: Interplay Between Necroptosis Apoptosis Pyroptosis and mentioning
confidence: 99%
“…It is unclear whether MLKL is involved in this process [ 87 ]. However, a recent paper showed that MLKL promoted intestinal epithelial barrier function by enhancing inflammasome activation [ 70 ].…”
Section: Necroptosis and Inflammationmentioning
confidence: 99%
See 1 more Smart Citation